Advancing Rural Tourism through Stronger Local Leadership and Improved Governance Capacity - Hakim Sulistyo; Sakir (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
Sustainable rural tourism relies heavily on the role of local leadership and the quality of governance in managing environmental, social, and economic resources. This study examines how local leaders in JatimulyoTourism Village, Kulonprogo, exercise governance functions to promote sustainable tourism practices while facing various institutional and community challenges. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving village leaders, tourism managers, and community groups. The findings show that local leadership plays a central role in building collaborative networks among stakeholders and in fostering community participation. However, governance implementation remains constrained by limited institutional capacity, uneven coordination among local actors, and the absence of long-term strategic planning. The study concludes that strengthening adaptive and participatory governance is crucial to ensure that rural tourism contributes to sustainability and local empowerment. This research provides practical insights for policymakers in designing governance models for sustainable tourism development in rural Indonesia.